PLAN DE MARKETING PARA LA EMPRESA “CARBONERO MIRADOR”, UBICADA EN LA CIUDAD DE LOJA. PERIODO OCTUBRE 2019 – MARZO 2020 - MALDONADO AJILA., KRUPSKAYA JOHANNA (2021)
SUMMARY This work is an analysis of the general environment, with which the PESTEC matrix was made. The same that is reflected in the evaluation matrix of external factors resulting in 3.00, value that is located above the measure; as main opportunities: Greater dissemination of services through the Internet and traditional methods, use of new technologies, etc.. The main threats are: Existence of rivalry among competitors, unemployment is maintained and growing, etc. Subsequently, an analysis of the competitive environment was carried out, in which Porter's five forces were used to determine the level of competitiveness, resulting in a CPM of 3.00, with the company in a good position but with room for improvement, the most important indicators being price, facilities, location and service. The internal analysis included market research to determine the company's strengths and weaknesses, with the following being the main strengths: it has appropriate facilities, strategic location, etc. As weaknesses: lack of advertising of all services, the company does not have a system for evaluating results, etc. With the development of the EFE and EFI matrix, the SWOT matrix was developed, which allowed the development of the Ansoff matrix and established the strategies for portfolio, penetration, development of new markets, segmentation and positioning. Finally, the marketing plan proposal was designed, developing the aforementioned strategies, making use of ATL and BTL marketing tools.